2008
DOI: 10.2174/1874300500802010043
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Immediate Tracheal Extubation After Liver Transplantation - A Single Center Experience

Abstract: Fast tracking approaches in liver transplantation include postoperative extubation immediately after surgery in the operating theatre. Based on the experience of 837 liver transplantations performed between 01/97 and 05/05, we report on the safety and feasibility of this procedure in almost 80% of transplant recipients, without increasing the incidence of subsequent reintubation (11%). This patient population experienced significantly higher survival compared to patients in whom extubation succeeded at the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Conversely, those in the delayed extubation group had a mean postoperative intubation duration of 3.2 days and a reintubation rate of 11.5%. Other reports have confirmed that patients who remained intubated post‐transplant had considerably higher rates of reintubation 18,19 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Conversely, those in the delayed extubation group had a mean postoperative intubation duration of 3.2 days and a reintubation rate of 11.5%. Other reports have confirmed that patients who remained intubated post‐transplant had considerably higher rates of reintubation 18,19 …”
Section: Discussionmentioning
confidence: 94%
“…Other reports have confirmed that patients who remained intubated posttransplant had considerably higher rates of reintubation. 18,19 Few studies have evaluated the effect immediate extubation may convey on postoperative recovery. By performing immediate extubation, patients likely experience improved early mobility, reduced overall sedation and analgesia requirements, decreased postoperative positive pressure ventilation, and improved hemodynamics, all of which can impact early postoperative recovery.…”
Section: 0% P < 001) (Table 3)mentioning
confidence: 99%
“…14 In contradiction to our study, Hoffmeister and colleagues declared no statistically significant difference between the two groups as regards the duration of surgery. 1 Also, Biancofiore et al found that the duration of surgery had no significant influence on the time of extubation. 6 …”
Section: Discussionmentioning
confidence: 99%
“… 12 Hoffmeister and colleagues found a highly significant difference in the amount of intraoperative transfused blood products between the extubated and non-extubated groups. 1 Zeyneloglu et al, when comparing extubated with non-extubated patients, found that those extubated had lower transfusion requirements. 13 Blood transfusion requirements were lower in our study, which may be attributed to the routine use of cell salvage, lower triggers for transfusion and different surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation